A Research on Fertility, Herd Life, Milk Production and Milk Quality Characteristics of Simmental (Fleckvieh) Cows: 1. Reproduction, Herd Life and Milk Production Characteristics - Atakan Koç; Mehmet Öner (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to determine the fertility, herd life and milk yield characteristics of Simmental (SIM) cows of Austrian origin, which have increased the interest of cattle breeders in Türkiye in recent years. From the records of the farm between 2011 and 2021, the first calving age (FCA), calving interval (CI), herd life (HL), productive life (PL), lactation length (LL), lactation milk yield (LMY) and 305 days milk yield (305-dMY) were calculated. A total of 307 FCA, 619 CI, 212 HL and PL, 447 LL, 271 LMY and 497 305-dMY data were used. The means of FCA, CI, HL, PL, LL, LMY and 305-dMY for SIM cows were 842.35±5.30 days (28.1 months), 422.98±3.18 days, 75.48±1.72 months, 47.15±1.73 months, 363.52±3.52 days, 10,596±152 kg and 8647.0±58.0 kg, respectively. Based on the long FCA and CI averages of Austrian-origin SIM cattle, although it can be interpreted that there are some problems in terms of reproductive efficiency in the farm, finding long HL and PL and high milk yield, it can be said that the farm contributes to the increase of milk yield per cow by turning the negativity caused by the reproductive efficiency into an advantage.